2014
DOI: 10.1177/1420326x14531000
|View full text |Cite
|
Sign up to set email alerts
|

What are you saying? Challenges and opportunities for increasing visibility and understanding of indoor microbiological research

Abstract: This study identifies challenges that microbiologists who study built environments face in their efforts to increase public understanding and visibility associated with their research. More specifically, it offers an empirical assessment of these scientists’ perceptions of what people need to understand – specific research terms and concepts are noted – and what needs to be considered when communicating with key decision-makers in agencies that fund research. The results of semi-structured interviews with 79 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…While research on science communication training appears rare, one related body of research has found that scientists continue to think about communication in relatively simplistic or problematic ways. This work focuses on scientists’ attitudes toward engagement and includes a range of qualitative (e.g., Blok, Jensen, & Kaltoft, 2008; Davies, 2008; Maranta, Guggenheim, Gisler, & Pohl, 2003) and quantitative research (Besley, 2015; Besley, Oh, & Nisbet, 2013; Dudo, Kahlor, AbiGhannam, Lazard, & Liang, 2014; Dunwoody, Brossard, & Dudo, 2009; Kahlor, Dudo, Liang, & AbiGhannam, 2015; Peters et al, 2008). A summary of initial work in this area concluded that scientists have relatively negative opinions about the public and journalists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While research on science communication training appears rare, one related body of research has found that scientists continue to think about communication in relatively simplistic or problematic ways. This work focuses on scientists’ attitudes toward engagement and includes a range of qualitative (e.g., Blok, Jensen, & Kaltoft, 2008; Davies, 2008; Maranta, Guggenheim, Gisler, & Pohl, 2003) and quantitative research (Besley, 2015; Besley, Oh, & Nisbet, 2013; Dudo, Kahlor, AbiGhannam, Lazard, & Liang, 2014; Dunwoody, Brossard, & Dudo, 2009; Kahlor, Dudo, Liang, & AbiGhannam, 2015; Peters et al, 2008). A summary of initial work in this area concluded that scientists have relatively negative opinions about the public and journalists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 2006 study done by the Royal Society in the United Kingdom found that 74% of scientists surveyed had “take(n) part in at least one science communication or public engagement activity in the past 12 months” (7). A survey of researchers who study microbiology of the built environment indicated that about 75% served as information sources for the public (8). …”
Section: Editorialmentioning
confidence: 99%
“…Kahlor and colleagues ( 37 ) provided what is, to our knowledge, the first empirical study that examined microbiologists and public communication. The researchers conducted semi-structured interviews with 79 US-based scientists who conduct indoor microbiological research.…”
Section: [Introductionmentioning
confidence: 99%